Bioactive peptides from meat: Current status on production, biological activity, safety, and regulatory framework. (November 2022) - Madhu, Madhuja; Kumar, Deepak; Sirohi, Ranjna; Tarafdar, Ayon; Dhewa, Tejpal; Aluko, Rotimi E.; Badgujar, Prarabdh C.; Awasthi, Mukesh Kumar
Abstract: By-products of the meat processing industry which are often discarded as waste are excellent protein substrates for producing bioactive peptides through enzymatic hydrolysis. These peptides have tremendous potential for the development of functional food products but there is scanty information about the regulations on bioactive peptides or products in various parts of the world. This review focuses on the diverse bioactive peptides identified from different meat and meat by-products, their bioactivity and challenges associated in their production as well as factors limiting their effective commercialization. Furthermore, this report provides additional information on the possible toxic peptides formed during production of the bioactive peptides, which enables delineation of associated safety and risk. The regulatory framework in place for bioactive peptide-based foods in different jurisdictions and the future research directions are also discussed. Uniform quality, high cost, poor sensory acceptance, lack of toxicological studies and clinical evidence, paltry stability, and lack of bioavailability data are some of the key challenges hindering commercial advancement of bioactive peptide-based functional foods. Absorption, distribution, metabolism and excretion (ADME) studies in rodents, in vitro genotoxicity, and immunogenicity data could be considered as absolute pre-requisites to ensure safety of bioactive peptides. In the absence of ADME and genotoxicity data, long term usage to evaluate safety is highly warranted. Differences in legislations among countries pose challenge in the international trade of bioactive peptides-based functional foods. Harmonization of regulations could be a way out and hence further research in this area is encouraged. Graphical abstract: Image 1 Highlights: Bioactive peptides from meat can exert positive physiological effects. Numerous production challenges are hindering development of bioactive peptide-based foods. Safety studies on bioactive peptides are highly warranted. Harmonization of regulatory framework may encourage more research.